The Hubungan Pola Asuh Orangtua Bekerja Dengan Tingkat Kemandirian Anak Usia Prasekolah Di TK Angkasa Adisutjipto - Aisya Billa Chery Oktavia Oktavia; Dwi Susanti (HEALTHY BEHAVIOR JOURNAL, 2025)
Background : Preschool children are often referred to as the critical period or golden age. The role of parents has great significance in facilitating the development of children's independence through implementing appropriate parenting patterns so that parents know the level of independence that the child has. Inappropriate parenting patterns can be a factor that causes developmental delays in children. Objective : To determine the relationship between working parents' parenting styles and the level of independence of preschool-aged children at Angkasa Adisutjipto Kindergarten. Methods : This research uses quantitative methods with a cross sectional approach. Sampling using techniques purposive sampling with a total of 44 respondents who met the inclusion criteria. The instruments used in this research include questionnaires Parenting Style Questionaire (PSQ) and preschool children's independence level questionnaire. Statistical analysis using Spearman Rank test with a significance level of p value <0.05. Results : The results of the research show that the highest level of children's independence is in the sufficient category, it’s 28 children (63.6%) and the parenting style of parents mostly applies a democratic parenting pattern, actually 37 respondents (84.1%). The results of the analysis obtained a significance value of 0.030 with a correlation coefficient value of 0.328. This means that the significant value obtained is smaller than 0.05 Conclusion : There is a significant relationship between the parenting style of working parents and the level of independence of preschool-aged children at Angkasa Adisutjipto Kindergarten